Pentingnya Penguasaan Bahasa Arab Bagi Pendakwah - Fathoni Fathoni (MODELING: Jurnal Program Studi PGMI, 2021)
Arabic language was chosen by Allah the Almighty as the official language of the last religion, Islam. Undoubtedly, Muslims are supposed to be found of Arabic language and to make every possible effort to learn this holy language. Allah the Almighty sorted out Arabic as Quranic language because it is the best of the existing languages. By mastering Arabic language, we could access abundant Islamic heritages, especially in classical books such as: science, philosophy, theology, and so on. Mastering Arabic language is thus very important, especially for Islamic preachers (da’i) without which they could not understand Islamic basic tenets, Al-Qur’an and Hadith. Psychologically, mastering Arabic language would optimize the effectiveness of dakwah, particularly in transmitting Islamic knowledge to the ummah.